Perfluoro-tert-butanol: a cornerstone for high performance fluorine-19 magnetic resonance imaging. Issue 63 (20th July 2021) - Wu, Tingjuan; Li, Anfeng; Chen, Kexin; Peng, Xingxing; Zhang, Jing; Jiang, Mou; Chen, Shizhen; Zheng, Xing; Zhou, Xin; Jiang, Zhong-Xing
Abstract : With nine equivalent  19 F and a modifiable hydroxyl group,  perfluoro- tert -butanol has outperformed most perfluorocarbons as a valuable building block for high performance  19 F MRI agents. Abstract : As a versatile quantification and tracking technology, 19 F magnetic resonance imaging ( 19 F MRI) provides quantitative "hot-spot" images without ionizing radiation, tissue depth limit, and background interference. However, the lack of suitable imaging agents severely hampers its clinical application. First, because the 19 F signals are solely originated from imaging agents, the relatively low sensitivity of MRI technology requires high local 19 F concentrations to generate images, which are often beyond the reach of many 19 F MRI agents. Second, the peculiar physicochemical properties of many fluorinated compounds usually lead to low 19 F signal intensity, tedious formulation, severe organ retention, etc. Therefore, the development of 19 F MRI agents with high sensitivity and with suitable physicochemical and biological properties is of great importance. To this end, perfluoro- tert -butanol (PFTB ), containing nine equivalent 19 F and a modifiable hydroxyl group, has outperformed most perfluorocarbons as a valuable building block for high performance 19 F MRI agents. Herein, we summarize the development and application of PFTB-based 19 F MRI agents and analyze the strategies to improve their sensitivity and physicochemical and biological properties. In the context of PFC-based 19 F MRI agents, we also discuss the challenges and prospects of PFTB-based 19 F MRI agents.